Understanding the dynamics of private medical insurance uptake: a cross-sectional survey among social media users in Kenya - Okaka, D. (Strathmore University, 2024)
Kenya aims to achieve Universal Health Coverage (UHC) by 2030, ensuring access to quality health services without financial hardship. Various prepayment mechanisms like private health insurance (PHI) can mitigate catastrophic health spending, yet their uptake remains low. This study examined factors influencing PHI uptake in Kenya through a cross-sectional analytic study with 440 participants (235 female, 205 male) aged 18-59 years. It aimed to provide context-specific evidence on strategies that can be tailored to increase the uptake of private medical insurance in Kenya. Study data was collected via an online self-administered survey, and both bivariate and multivariable logistic regression analyses were conducted to ascertain relations between various variables in the study. A thematic analysis was also done to explore the challenges mentioned in accessing PHI via feedback from social media users. The study found that 70% of respondents had PHI, most of which was employer-provided. Although not reaching a statistical significance, PHI ownership peaked among those aged 30-39 years and was positively associated with higher monthly household income. The key barriers found to the uptake of PHI included a lack of information, high cost of premiums, lack of trust in the PHIs, and complex claim processes. Despite the high coverage in the study sample, gaps still remain for achieving universal coverage. The recommendations to PHIs include differentiated pricing strategies, reducing premiums altogether, targeting older adults and the informal sector, improving transparency, and enhancing communication. However, PHI alone may not achieve UHC, as evidenced from this study and others; thus, a tax-funded system should be considered for significant progress towards UHC.
Full - text thesis